Salt marsh response to changing hydrodynamics: the case of Ancão Inlet migration (Ria Formosa coastal lagoon) - Amado, Pedro Miguel de Sousa Vinagre (2020)
Concerning the economic and ecological importance of salt marshes, it is of extreme importance to improve our knowledge on the physical processes involved with marsh evolution, as well as the limits and degree of interaction with the surrounding sedimentary sources. The studied salt marsh area is located fronting Ancão Inlet, in the western sector of the Ria Formosa barrier system. A 67-year time series of aerial photographs and ortho-photographs, between 1947 and 2014, was used to infer salt marsh sedimentary evolution (progression or recession) in relation to natural inlet migration and to its relocation in 1997. The following morphologies were mapped: salt marsh, tidal flat, sand banks, and inlet flood delta. The results focus on the analysis of horizontal displacement of these morphologies over time. It was noted that in general, the Salt Marsh presents a growth of its area along time. The different stages of the Ancão inlet migration and the consequent distance to the inlet throat is a limiting factor for salt marsh growth. The sand banks and flood deltas are the main sediment feeders of the Tidal Flat growth. The contribution of the Ancão inlet to the Tidal Flat growth was more significant when the inlet starts reaching its closure phase. The growth of Tidal Flat is an opportunity for salt marsh development